Application Of Project-Based Learning Models In Learning To Write Proposal In Semester V Students - Susetyo Susetyo (Al-Makki Publisher, 2023)
The purpose of this study was to determine the effect of the project-based learning model on the ability of Indonesian Language and Literature Education Study Program students in preparing quantitative research proposals . This research method is an experiment with the One Group Pretest-Posttest Design . All students of the Indonesian Language and Literature Education Study Program who took the Indonesian language education research course in the odd semester of the 2022/2023 academic year were used as research subjects. The instruments used to collect research data are (1) the research proposal assessment rubric. Data collection techniques were in the form of (1) assignments, namely making quantitative research proposals in Indonesian language and literature education. The collected data were analyzed using quantitative data analysis techniques using percentage and comparison formulas. The results showed that the project-based learning model had an effect on the ability of fifth semester students of the Indonesian Language and Literature Study Program in preparing quantitative research proposals. The ability of fifth semester students of the Indonesian Language and Literature Education Study Program FKIP PGRI Yogyakarta University who have participated in the implementation of project-based learning has the ability to write quantitative research proposals higher than the ability of students before participating in project-based learning. Research results are made into scientific journal articles and published in reputable or accredited international journals.